THE SYSTEM FOR QUICK MONITORING OF ASTRONOMICAL PLATE ARCHIVES. MAIN PRINCIPLES AND PURPOSES. - Sergeev, A. V.; Sergeeva, T. P. (Одеські астрономічні публікації, 2017)
We propose to create a system for quick search and analyses of astronomical events and objects in plate archive of the Ukrainian Main astronomical observatory of NAS. The proposed idea of effective restoring of astronomic information is based on the treatment of the digitized plate archive as whole. The plates will be digitized by commercial scanner with optical resolution of 20 mkm and resolution on amplitude of 4096 grey levels. Such scanning parameters give the opportunity to receive the plate image les of the reasonable sizes suitable enough to identify the required object and to define its precise photometric characteristics. Connection of the system to Internet will allow a remote user to have access to plate images archive and to work with it. Modular structure of the system basic software and standard format of the plate image les allow future development of problem-oriented software for special astronomical researches by means of the cooperative projects.